Shiva idol beneath the Banyan tree - Ghosh, Ayan (2023)
Banganga Tank has several legends associated with it, and they have diverse origins. With the passage of time, memories of local incidents have been intertwined with these origin myths. One such prevailing story is how the original lingam at Walkeshwar Temple was lost to the sea to avoid desecration by mlecchas (referring to Muslim and Christian rule under the Gujarat Sultanate and the Portuguese). Based on this belief, on the day of Mahashivratri, the Koli fishing community venture out to sea to offer prayers to the vanished lingam.